Prisms for pain. Can visuo‐motor rehabilitation strategies alleviate chronic pain?. (11th June 2015) - Torta, D.M.; Legrain, V.; Rossetti, Y.; Mouraux, A.
Abstract: Background and aims: Prism adaptation (PA) is a non‐invasive procedure in which participants perform a visuo‐motor pointing task while wearing prism goggles inducing a lateral displacement of the visual field and a mismatch between the seen and felt position of the pointing hand. PA is thought to induce a reorganization of sensorimotor coordination, and has been used successfully to rehabilitate neglect following right‐hemisphere lesions. Because studies have shown that complex regional pain syndrome (CRPS) is associated with neglect‐like symptoms, it was proposed that PA could be used to alleviate pain in these patients. Database: A search for peer‐reviewed articles on neglect‐like symptoms in CRPS and on the use of prisms in CRPS was conducted using the PubMed database. Results: There is still no agreement as to whether CRPS patients really present neglect symptoms and, if they do, what it is that they neglect. Furthermore, there is insufficient data to determine whether PA exerts an effect on CRPS symptoms. Finally, it remains unknown whether neglect can be observed in other types of lateralized pain, or whether PA could be useful for these patients. Conclusion: By highlighting open issues, our review provides guidelines for future studies on the use of prisms in pain. The assessment of neglect in patients with CRPS as well as other types of lateralized chronic pain should be characterized using a combination of neuropsychological methods assessing the multiple aspects of neglect in a more refined manner. In addition, further studies should investigate the mechanisms through which PA may modulate pain.